Evaluation of post-operative outcome of non-descent vaginal hysterectomies done in a year at a tertiary care centre - Juhitha, Bammidi; Ramalingam, K.; Suprada, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim of our study is to represent our experiences with non-descent vaginal hysterectomies (NDVH), the intraoperative and postoperative complications of NDVH, using suture less procedure and only energy sources like cautery, assess intra operative blood loss, operative time, risk of infection, post op hospital stay. The objective was to assess the outcomes of the safest and scar less method of hysterectomy i.e. NDVH, practised at a tertiary centre in one-year period of time. Methods: This was a retrospective case study conducted in the department of obstetrics and gynaecology of NRI Medical College and Hospital, Mangalagiri, over a period of 12 months (October 2022 to October 2023). This includes 50 patients who underwent non-descent vaginal hysterectomy for benign indications with adequate vaginal access, with good mobility, without any suspected adnexal pathology and without uterine prolapse. Results: All 50 cases were studied retrospectively. None of them had bladder injury, or need for conversion to abdominal route. Commonest indication for surgery was fibroid uterus. Average duration of surgery was 1.2 hours. Average blood loss was 49 ml. Post-operative complications were minimal. Average hospital stay was 4.3 days. Patient mobility and ambulation was early, with minimal need for pain relief. Conclusions: The study concludes that patients requiring hysterectomy for benign uterine pathologies without prolapse can be given an option of non-descent vaginal hysterectomy, because of the advantages that it has, over the abdominal route.